Comparative Analysis of Gut Microbiota in Centenarians and Young People: Impact of Eating Habits and Childhood Living Environment - Sepp, Epp; Smidt, Imbi; Rööp, Tiiu; Štšepetova, Jelena; Kõljalg, Siiri; Mikelsaar, Marika; Soidla, Indrek; Ainsaar, Mare; Kolk, Helgi; Vallas, Mirjam; Jaagura, Madis; Mändar, Reet (Frontiers in Cellular and Infection Microbiology, 2022)
The composition of centenarians’ gut microbiota has consistently been used as a model for healthy aging studies. However, there is an incomplete understanding of how childhood living conditions and eating habits affect the development and composition of gastrointestinal microbiota in centenarians with good cognitive functions. We compared the gut microbiota as well as the living and eating habits of the oldest-old group and the young people group. The richness and diversity of microbiota and the abundance of hereditary and environmental microbes were higher in people with longevity than young people. People with longevity ate more potatoes and cereal products. In their childhood, they had more exposure to farm animals and did not have sewers compared with young people. Young people’s gut microbiota contained more butyrate-producing bacteria and bacteria that characterized an animal-based Western diet. These results expand our understanding of the effects of childhood environment and diet on the development and stability of the microbiota in people with longevity.